A domain decomposition approach for static and dynamic analysis of composite laminated curved beam with general elastic restrains. Issue 16 (18th August 2019) - Guo, Jianghua; Shi, Dongyan; Wang, Qingshan; Pang, Fuzhen; Liang, Qian
ABSTRACT: A formulation for static and dynamic vibration analysis of composite laminated curved beams is presented by using an efficient domain decomposition method. Multi-segment partitioning strategy is used to accommodate the accurate requirements of responses. The system potential functional is introduced to satisfy the continuity constraints on the segment interfaces. The Chebyshev orthogonal polynomials are used as displacement admissible functions. The theoretical results are verified by comparing with those previously published in literature, and the ones obtained by using the program ABAQUS. Based on the verification, the parametric study of composite laminated curved beam is carried out.